Perspectives of secondary school teachers on the strengths and limitations of digital mathematics textbooks: an exploratory research in China - Tommy Tanu Wijaya; Yiming Cao; Xiaoyu Xiao; Imam Fitri Rahmadi; Yunpeng Gong (Humanities & Social Sciences Communications)
Abstract Wide developments in technology provide major changes and opportunities for digital mathematics textbooks. In this context, the swift incorporation of digital textbooks into educational frameworks explores the potential and limitations of enriching mathematical understanding and instructional methodologies. Therefore, this research aimed to analyze the perspectives of secondary school teachers in China on the strengths and weaknesses of digital mathematics textbooks for learning. An exploratory analysis by semi-structured interviews was implemented with the participation of five secondary school teachers who attended training and used digital mathematics textbooks. Thematic analysis was conducted, and coding was used as the basic analytic strategy. The results showed that digital mathematics textbooks were supportive instructional media capable of supporting different teaching and learning activities as well as visualizing concepts. These media were considered simple and practical as well as valuable to strengthen teaching skills with technology. However, textbooks possessed minimum pedagogical features, practices, and interfaces. The results also reported the need to incorporate more pedagogical tools and interactive elements within textbooks to enhance educational value. Furthermore, these insights called for ongoing professional development to effectively integrate and use digital textbooks in pedagogy.